A novel problem, a tested solution: A case of an infected left ventricular titanium plug. Issue 11 (13th August 2020) - Teelucksingh, Sachin; Schueler, Stephen; Crowley, Timothy P.; Ragbir, Maniram
Abstract: Persistent infection of left ventricular‐assisted devices are challenging to treat. We describe a case of a middle‐aged man who presented with cardiogenic shock and profound heart failure from sarcoid myocarditis, necessitating the placement of a left ventricular assist device. After recovery of cardiac function, the device was decommissioned but complicated by infection in the implant bed, chest wall, and of the titanium plug left in situ. This to our knowledge is the first report of an infected titanium plug and we describe an option of using a latissimus dorsi flap using its vascularized tissues to treat the infected plug. This is another example where a multidisciplinary approach can yield rewarding results in cases such as these.